Two-warehouse system for non-instantaneous deterioration products with promotional effort and inflation over a finite time horizon - M. Palanivel; S. Priyan; P. Mala (Journal of Industrial Engineering International, 2018)
In the current global market, organizations use many promotional tools to increase their sales. One such tool is sales teams' initiatives or promotional policies, i.e., free gifts, discounts, packaging, etc. This phenomenon motivates the retailer/or buyer to order a large inventory lot so as to take full benefit of promotional policies. In view of this the present paper considers a two-warehouse (owned and rented) inventory problem for a non-instantaneous deteriorating item with inflation and time value of money over a finite planning horizon. Here, demand depends on the sales team's initiatives and shortages are partially backlogged at a rate dependent on the duration of waiting time up to the arrival of next lot. We design an algorithm to obtain the optimal replenishment strategies. Numerical analysis is also given to show the applicability of the proposed model in real-world two-warehouse inventory problems.
Keywords: 650; Promotional effort; Two-warehouse; Non-instantaneous; Finite horizon; Inflation